An early 17th-century ‘half-carvel‘ construction in the North Frisian Wadden Sea: The Japsand wreckage near Hallig Hooge, Germany - Zwick, Daniel (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
This paper outlines the research results of a recent discovery of two early 17th century wreck fragments of a mixed clinker and carvel construction – a so-called ‘half carvel’ – at the Japsand, an outer shoal of the island of Hooge in the North Frisian Wadden Sea, Germany. The description is followed by a discussion on how this find could be contextualised in terms of a northern European shipbuilding tradition and ship-type. This paper advocates that ‘half-carvels’ ought to be seen as part of a broader phenomenon of carvel-analogous shell-first lapstrake constructions prevalent in the Baltic Sea and beyond.